INVENTARISASI DAN IDENTIFIKASI HAMA DAN PENYAKIT UTAMA TANAMAN JAGUNG (Zea mays L.) - Emanuel Randy Dhena; Yustina Maria Silvia Wonga Puu (Agriculture Faculty of Flores University, 2011)
This research was carried out in order to understand the main types of pests and diseases that affect corn, which types are most dominant and to understand the severity of these main diseases in corn. Observation of variables involved the identification of pests and diseases that attacked corn plants, the diversity of these pests and diseases as well as the intensity of the damage caused by these pests and diseases. The results of this research showed that the main type of pest and disease that attacks corn are, among others: seedling flies (Atherigonasp), grasshoppers (Oxyasp), corn stalk drillers (Ostrineafurnacalis) and leaf rust. The most dominant type of pest or disease were grasshoppers (Oxyasp) which attacked plant leaves. The seriousness of an attack by a pest or disease was found to be important in the seedling phase, there are many variations in between species of corn and also developed with the age of the corn. At 12 days after planting, the incidence of insect attack was0.2% and at 33 days and 54 days after planting it was 0.32-0.47%. Whereas for disease, when observed at 33 and 54 days after planting, the average incidence of disease attack was 0.05-0.23%. Also, when observed at 61 days and 75 days, the incidence of attack rose to 0.32-40%.